What is the association between the ethnic composition of neighbourhoods, workplaces and schools and the formation of mixed-ethnic unions? - Puur Allan; Rahnu Leen; Tammaru Tiit (Wiley, 2022)
Although ethnic diversity and the types of interpersonal ties that are experienced in various domains of life may vary considerably, studies regarding the local marriage market rarely focus on the relationship between the formation of mixed-ethnic unions and the ethnic composition of more than one spatial context. In this study, by applying event history analysis methods to longitudinal register data from Finland, we address three spatial contexts: residential neighbourhoods, workplaces and schools. The main finding is that getting in contact with natives in all three spatial contexts elevates the probability of the formation of a mixed-ethnic union between migrants and natives. Exposure to natives in residential neighbourhoods and workplaces does not lose its relevance for partnership outcomes among immigrants who have arrived in the host country as children, or among the descendants of immigrants. On the contrary, the effects that can be associated with higher concentrations of immigrants in neighbourhoods and workplaces tend to increase in strength for the second generation rather than decrease.